Pembentukan kompetensi ekologis dengan model pembelajaran kontekstual dan berbasis masalah dalam PPKn di SMP - Pertiwi, Shinta; Samsuri, Samsuri (Universitas Negeri Yogyakarta, 2017)
This research based article was aimed at explaining the effect of Contextual Teaching and Learning and Problem Based Learning on the establishment of Ecological Competence in Civic Education in Junior High School. It was a quasi-experiment research with pretest-posttest control group design. The population was student grade VII of SMP Negeri 2 Surakarta. The sample was chosen randomly, consist of one classroom as experimental group and another classroom as control group. Instrument for collecting data were test, questionnaire, and observation. It can be concluded that the establishment of ecological competence among junior high school students though through contextual teaching and learning are more effective than those who were though by problem based learning and conventional one. It was indicated by the result of one way anova Fcount >Ftable (24.031>3.11) and P=0.000<0.05).